Preparation and Characterization of PDLLA-PCL-Starch Blends Processed Under Microwave Radiation - Singla, Ritika (My University, 2011)
Properties of biodegradable polymers like PDLLA and PCL can be modified by blending them with each other and with other polymers like Starch. In the present study we have prepared blends pf PDLLA, PCL and Starch in different proportions and then subjected to microwave radiation. Using microwave time of reaction has been reduced to 3-30 min as microwave is associated with more even distribution of heat. To characterize the blends various techniques like FTIR has been used. On blending PDLLA, PCL and starch in various ratios using chloroform as a solvent and subjecting the mixtures to microwave radiation, it becomes clear from FTIR spectra that O-H and C=O regions of the blend show significant variance after microwave irradiation compaired to the parent polymers. The results indicate a direct linkage between the polymers indicating the formation of a chemical linkage between the two molecules as opposed to just a phyical blend.
M.Tech. (Chemical)
Keywords: PDLLA; PCL; Starch; Blends; Microwave